Budgetary influence under information asymmetries: Evidence from Nigeria’s subnational agricultural investments - Mogues, Tewodaj; Olofinbiyi, Tolulope (Elsevier, 2020)
With emerging recognition of changing climates’ impact on agricultural productivity, a sharper lens is focused on how to target agricultural public investments for development. This paper contributes to an understanding of budget decision-making processes in agricultural development, by examining to what extent those with superior information and expertise on a sector have sway over how public resources to the sector are allocated. The empirical qualitative analysis of this paper employs process tracing with an embedded case study design, based on interviews of 79 senior public sector key-informants in Nigeria. We also analyzed quantitative public expenditure data in the study areas. We draw insights from theories of information asymmetries in the public sector along three dimensions. Within the first type of information asymmetry, we find that, despite the higher agricultural technical expertise that sector bureaucrats have vis-à-vis the elected non-sector-specific chief executives, it is the latter who heavily influence agricultural resource allocation. In the second form of information asymmetry, the benefits from superior lower-tier information are only exploited at one subnational (state) level but not at the other (local government) level. Within the third kind of information asymmetry, public leaders prioritize funding for those types of public investments that are more visible by their nature, and outputs of which materialize relatively rapidly; this disfavors agriculture. Going beyond the literature on the impact of information interventions, this study sheds light on the extent to which information already in the public sector is tapped into to guide the provision of public goods and services.